Role of Tangible Reward and Intangible Reward on Millennials’ Job-Hopping Behavior in Kathmandu Valley - Poudel, Nistha; Ojha, Aarati (Nepalese Journal of Management Science and Research, 2026)
This study investigates the effects of tangible and intangible rewards on job-hopping behavior among millennials in the Kathmandu Valley, aiming to identify which type of reward is most effective in retaining young employees in a transforming work environment. Adopting an explanatory research design, data were collected via structured online questionnaires from 408 millennial employees across various industries, using convenience sampling. The relationships were analyzed using Structural Equation Modeling (SEM) with Smart-PLS 4. The findings indicate that both tangible rewards such as salary and financial benefits and intangible rewards such as recognition and career development opportunities significantly reduce job-hopping behavior among millennials. However, tangible rewards demonstrate a comparatively stronger influence in lowering turnover intentions than intangible rewards. The model shows a very high level of explanatory power, indicating that reward-related factors account for a substantial proportion of millennials’ job-hopping decisions. These results suggest that while financial incentives are the most influential factor in discouraging turnover, non-financial rewards also play a meaningful and complementary role in employee retention. The study only captures data at a single point in time and does not consider changes in job-hopping behavior or perceptions of rewards over several years. As a result, the findings represent only a temporal snapshot of the respondents' experiences and attitudes.